(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
This action research was developed with teachers and students from the Modern Languages ​program at the University of Quindio. An intervention strategy was designed to improve the performance of individual participants in regards to their written skills. The strategy aimed at providing a clear explanation of the mistakes found, placing the student into a position to consciously avoid them in future writings. The categories that emerged from the instruments and procedures performed were: utility, content and evaluation, showing that this proposal is an efficient alternative to improve English writing.